2012
DOI: 10.1155/2012/313275
|View full text |Cite
|
Sign up to set email alerts
|

TPEN Induces Apoptosis Independently of Zinc Chelator Activity in a Model of Acute Lymphoblastic Leukemia andEx VivoAcute Leukemia Cells through Oxidative Stress and Mitochondria Caspase-3- and AIF-Dependent Pathways

Abstract: Acute lymphoblastic leukemia is still an incurable disease with resistance to therapy developing in the majority of patients. We investigated the effect of TPEN, an intracellular zinc chelator, in Jurkat and in ex vivo acute lymphoblastic leukemia (ALL) cells resistant to chemotherapy. Changes of nuclei morphology, reactive oxygen species generation, presence of hypodiploid cells, phosphatidylserine translocation, mitochondrial membrane depolarization, immunohistochemical identification of cell death signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 64 publications
5
48
0
Order By: Relevance
“…AIF protein, which is located in the mitochondrial intermembrane space, exhibits apoptosis-inducing activity (34). In response to apoptotic stimuli, AIF molecules are released from the mitochondria into the cytoplasm followed by translocation to the nucleus and subsequent integration with chromosomal DNA, which leads to chromosome condensation and DNA breakage into large fragments (~50 kB) (35).…”
Section: Discussionmentioning
confidence: 99%
“…AIF protein, which is located in the mitochondrial intermembrane space, exhibits apoptosis-inducing activity (34). In response to apoptotic stimuli, AIF molecules are released from the mitochondria into the cytoplasm followed by translocation to the nucleus and subsequent integration with chromosomal DNA, which leads to chromosome condensation and DNA breakage into large fragments (~50 kB) (35).…”
Section: Discussionmentioning
confidence: 99%
“…7). TPEN, a known cytotoxic compound (38)(39)(40), was used as a positive control and showed toxicity at concentrations of Ͼ3.75 M, in agreement with previous findings (38,39). Most cyclic peptomers were not cytotoxic to HeLa cells, except for EpD-4=N, which showed toxicity at concentrations of Ͼ102 M. In addition, EpD-1N-treated cells displayed low absorbance in the MTT [3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide] assay at all concentrations, for reasons that are unclear but may reflect the compound's physical properties under these conditions.…”
Section: Development and Use Of An Nf-b-gfp Stable Cell Line For Idenmentioning
confidence: 99%
“…Zinc plays an important role in the regulation of apoptosis. It has been shown that the addition of Zn 2+ -chelators leads to apoptosisinduction in various hepatocytes, as well as in leukemia cells (33,34). Sequestering inhibitory Zn 2+ ions in inactive procaspase-3 generates active caspase-3, which subsequently triggers the downstream effector caspase-6 and induces apoptosis (33).…”
Section: +mentioning
confidence: 99%